Bektashi Sufi order An Analytical Study - Jabbar Nasser Yousef ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Bektashi Sufi order is an analytical and descriptive study that may be a pioneer in this field in explaining the foundations and rules on which that order was based, which can be recognized as a Shiite order that has achieved a significant spread in the Sunni community.  The study aims to dismantle the beginnings and roots of this method and identify the changes that occurred in it compared to what it was at the time of its founding, then try it fundamentally to show the extent of its conformity with the doctrinal rules and foundations. Revealing the identity of the members of the Bektashi order and following up on their path and the extent of their growing belief in the order is one of the determinants that imposed its presence in the study due to the peculiarities and doctrinal entanglements. However, its most important feature is its proximity to the world of Ahl al-Bayt (peace be upon them) in terms of loving them and disavowing their enemies. Despite the scarcity of sources that dealt with the subject of the study in the Arabic language, most of which were in Turkish and Persian, and the challenge this posed in providing the research with a comfortable flow of information and ideas, objective results were reached in the study that confirm that the Bektashi method is very close to the literature and principles of the Jaafari doctrine and that there are opportunities. There are many shared spaces that can be invested in guidance, advocacy, and containment, similar to the experience presented in this field by His Eminence, the authority of the sect, Mr. Mohsen Al-Hakim, may God Almighty be pleased with him.